documenta III : Handzeichnungen. - Branner, Karl; Haftmann, Werner (Kassel : Verlag Hessische Druck- und Verlagsanstalt GmbH, 1964)
Arp, Hans (Jean) ; Auberjonois, René ; Barlach, Ernst ; Baumeister, Willi ; Bazaine, Jean ; Beckmann, Max ; Bellmer, Hans ; Beuys, Joseph ; Bissier, Julius ; Boccioni, Umberto ; Bonnard, Pierre ; Braque, Georges ; Bresdin, Rodolphe ; Carrà, Carla ; Cézanne, Paul ; Chagall, Marc ; De Chirico, Giorgio ; Cimiotti, Emil ; Corinth, Lovis ; d'Orgeix, Christian ; Dado ; Dali, Salvador ; Derain, André ; Despiau, Charles ; Dix, Otto ; Dubuffet, Jean ; Duchamp, Marcel ; Dufy, Raoul ; Ensor, James ; Ernst, Max ; Fassbender, Joseph ; Feininger, Lyonel ; Giacometti, Alberto ; Gilles, Werner ; van Gogh, Vincent ; González, Julio ; Gorky, Arshile ; Gris, Juan ; Grosz, George ; Guys, Constantin ; Hartung, Hans ; Hegenbarth, Josef ; Hollegha, Wolfgang ; Jorn, Asger ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Kitaj, R.B. ; Klee, Paul ; Klimt, Gustav ; Kokoschka, Oskar ; Kubin, Alfred ; Lam, Wifredo ; Laurens, Henri ; Leger, Fernand ; Lehmbruck, Wilhelm ; Lismonde ; Lucebert ; Macke, August ; Maillol, Aristide ; Manessier, Alfred ; Marc, Franz ; Marcks, Gerhard ; Marini, Marino ; Marquet, Albert ; Masson, Andre ; Masurovsky, Gregory ; Matisse, Henri ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Mettel, Hans ; Meyer-Amden, Otto ; Michaux, Henri ; Miro, Joan ; Modersohn-Becker, Paula ; Modigliani, Amedeo ; Mondriaan, Piet ; Moore, Henry ; Morandi, Giorgio ; Munch, Edvard ; Nay, Ernst Wilhelm ; Nicholson, Ben ; Nolde, Emil ; Oelze, Richard ; Pascin, Jules ; Permeke, Constant ; Picasso, Pablo ; Pignon, Edouard ; De Pisis, Filippo ; Pollock, Jackson ; Redon, Odilon ; Réquichot, Bernard ; Rodin, Auguste ; Schiele, Egon ; Schlemmer, Oskar ; Schultze, Bernard ; Scipione ; Seurat, Georges ; Severini, Gino ; Signac, Paul ; Sironi, Mario ; Sonderborg, K.R.H. ; etc.
Documenta III, Internationale Ausstellung, Alte Galerie, Museum Fridericianum, Orangerie, Kassel, 27. Juni - 5. Oktober 1964
Duits
boek